Formulation development and optimization of palm kernel oil esters-based nanoemulsions containing sodium diclofenac - Rezaee, Malahat; Basri, Mahiran; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Chaibakhsh, Naz; Karjiban, Roghayeh Abedi (Dove Medical Press, 2014)
Response surface methodology was employed to study the effect of formulation composition variables, water content (60%–80%, w/w) and oil and surfactant (O/S) ratio (0.17–1.33), as well as high-shear emulsification conditions, mixing rate (300–3,000 rpm) and mixing time (5–30 minutes) on the properties of sodium diclofenac-loaded palm kernel oil esters-nanoemulsions. The two response variables were droplet size and viscosity. Optimization of the conditions according to the four variables was performed for preparation of the nanoemulsions with the minimum values of particle size and viscosity. The results showed that the experimental data could be sufficiently fitted into a third-order polynomial model with multiple regression coefficients (R2) of 0.938 and 0.994 for the particle size and viscosity, respectively. Water content, O/S ratio and mixing time, quadrics of all independent variables, interaction between O/S ratio and mixing rate and between mixing time and rate, as well as cubic term of water content had a significant effect (P<0.05) on the particle size of nanoemulsions. The linear effect of all independent variables, quadrics of water content and O/S ratio, interaction of water content and O/S ratio, as well as cubic term of water content and O/S ratio had significant effects (P<0.05) on the viscosity of all nanoemulsions. The optimum conditions for preparation of sodium diclofenac nanoemulsions were predicted to be: 71.36% water content; 0.69 O/S ratio; 950 rpm mixing rate, and 5 minute mixing time. The optimized formulation showed good storage stability in different temperatures.